Psychometric properties of the Brazilian version of the Canine Brief Pain Inventory (CBPI) for dogs with clinical signs of osteoarthritis and preliminary evidence of its clinical utility - Matsubara, L. M. [UNESP]; Teixeira, L. R. [UNESP]; Mesquita, L. R. [UNESP]; Landeira-Fernandez, J.; Anunciação, L.; Luna, S. P.L. [UNESP] (FapUNIFESP (SciELO), 2022)
This study aimed to determine the psychometric properties and clinical use of the Brazilian version of the Canine Brief Pain Inventory (CBPI) in dogs with hip dysplasia (HD). Forty-three dogs with HD and 16 clinically normal dogs were enrolled. The HD dogs were treated daily with 4.4mg/kg carprofen (GT = 21) or placebo (GP = 19), for four weeks. Owners completed the CBPI at two weeks (W-2) and immediately before the start of the treatment (W0), two (W2) and four (W4) weeks during treatment, and two weeks (W6) after the end of treatment. The internal structure was accessed, and the Cronbach’s alpha coefficient was 0.97, indicating the high internal consistency of the instrument. Principal Component Analysis (PCA) suggested the retention of one component, which accounted for 78% of the variability. The ROC curve analysis concluded that the score 3 has an excellent performance to discriminate between normal and possible HD dogs (AUC of 0.973). There was no difference between dogs treated with carprofen versus placebo. The instrument in Portuguese showed construct and criterion validity and reliability to be used in dogs with HD
Propriedades psicométricas da versão brasileira do Breve Inventário de Dor Canina (BIDC) em cães com sinais clínicos de osteoartrite e evidências preliminares da sua utilização clínica
Keywords: Chronic pain; Dogs; Osteoarthritis; Validation studies